PENGARUH CORPORATE SOCIAL RESPONSIBILITY, STRUKTUR MODAL, DAN UKURAN PERUSAHAAN TERHADAP RETURN ON EQUITY PADA SEKTOR INDUSTRI BARANG KONSUMSI PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2019 - Ni Luh Gede Kandel Semitha Dewi; I Gusti Agung Krisna Lestari; Sarita Vania Clarissa (Universitas Triatma Mulya, 2022)
Financial performance is important for every company in business competition to maintain its company. Performance measurement is needed to improve operational activities in order to be able to compete with other companies. This study aims to examine the effect of the variables Corporate Social Responsibility (CSR), Debt to Equity Ratio (DER), and Company Size (SIZE) on the Return On Equity (ROE) of manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. The manufacturing companies used in this study were 26 companies. The sample in this study amounted to 78 samples. Data were analyzed using descriptive analysis and multiple linear analysis. The results of the study revealed that the CSR and DER variables had a positive effect on financial performance, while the SIZE variable had no effect on financial performance.